2013
DOI: 10.1002/jgrd.50490
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant transport among California regions

Abstract: Several regions within California have significant air quality issues. Transport of pollutants emitted in one region to another region may add to the impact of local emissions. In this work, Lagrangian particle dispersion model simulations show the amounts of tracers that are transported within and among four regions, Southern California, the San Francisco Bay Area, the Central Valley, and the rest of the state. The simulations cover May and June of 2010, the California Research at the Nexus of Air Quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The height of the boundary layer may vary with wind speed (Oke, 1987), influencing the concentration and vertical profile of pollutants. The boundary layer not only controls transport and location of pollutants and aerosols but also their concentrations would be different in variable boundary layer structures (Angevine et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The height of the boundary layer may vary with wind speed (Oke, 1987), influencing the concentration and vertical profile of pollutants. The boundary layer not only controls transport and location of pollutants and aerosols but also their concentrations would be different in variable boundary layer structures (Angevine et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The WRF simulations were carried out using a configuration similar to the pollution transport simulations of Angevine et al (2013), with a horizontal resolution of 12 km, temporal resolution of 1 hour and 50 vertical levels. The sensitivity of back trajectories to the temporal and spatial resolution of meteorological data is discussed in Draxler (1987).…”
Section: The Weather Research and Forecasting Model (Wrf)mentioning
confidence: 99%
“…For this purpose the Advanced Research WRF (WRF hereafter) model version 3.5.1 (Skamarock et al, 2005;Skamarock and Klemp, 2008) was run with boundary-conditions from the half-degree Climate Forecast System (CFS) and CFSv2 (Saha et al, 2010(Saha et al, , 2013) with a change-over in 2011. Our configuration is similar to that used by Angevine et al (2013) and verification against surface observations confirmed that the WRF model was an improvement on using CFS or ERA-interim directly.…”
Section: Wind Speed and Direction Estimatesmentioning
confidence: 53%